ANALISIS KANDUNGAN Gamma Aminobutyric Acid (GABA), FENOL TOTAL DAN AKTIVITAS ANTIOKSIDAN “BERAS KECAMBAH” KULTIVAR LOKAL (Oryza sativa L.) DI YOGYAKARTA - Nurhening Yuni Ekowati; Yekti Asih Purwestri (AGRICOLA, 2016)
Rice is staple food in Indonesian and almost in all Asian. Germination is commonly method to increase nutritional content in grain and cereal. The aim of this research is to analyze gaba and total phenolic contents, and also antioxidant activity in germinated rice native cultivar from Yogyakarta. This research is also to determine the optimal condition in rice germination. Three native rice cultivars from Ngaglik Sleman Yogyakarta  used in this research, it were brown rice, red rice and black rice cultivars. Temperatures and soaking time variations used as treatments, rice without soaking treatment as controls.  The temperature variations was 28oC and 37oC and the  soaking time  was 6, 12, 18, and 12 hours. Three parameters GABA, total phenolic, and antioxidant activity was measured using spectrophotometric methods. The result of this research showed the cultivar that yield the highest GABA was black rice soaked in 37oC for 12 hour. It was 9,39 mg/100 g dry weight. Black rice without soaking treatment was the highest total phenolic content, it was 67,79 mg GAE/100 g dry weight with 7,91 ppm for IC50. The optimal condition was 37oC for 12 hour treated to Black rice that yield GABA 9,39 mg/100 g dry weight with total phenolic content and IC50 were 57,65 mg GAE/100 g dry weght  26,23 ppm, respectively.